Plant E3 Ligases and Their Role in Abiotic Stress Response - Raed Al-Saharin; Hanjo Hellmann; Sutton Mooney (Cells, 2022)
Plants, as sessile organisms, have limited means to cope with environmental changes. Consequently, they have developed complex regulatory systems to ameliorate abiotic stresses im-posed by environmental changes. One such system is the ubiquitin proteasome pathway, which utilizes E3 ligases to target proteins for proteolytic degradation via the 26S proteasome. Plants ex-press a plethora of E3 ligases that are categorized into four major groups depending on their structure. They are involved in many biological and developmental processes in plants, such as DNA repair, photomorphogenesis, phytohormones signaling, and biotic stress. Moreover, many E3 ligase targets are proteins involved in abiotic stress responses, such as salt, drought, heat, and cold. In this review, we will provide a comprehensive overview of E3 ligases and their substrates that have been connected with abiotic stress in order to illustrate the diversity and complexity of how this pathway enables plant survival under stress conditions.